Dose-dependent effects of GAT107, a novel allosteric agonist-positive allosteric modulator (ago-PAM) for the α7 nicotinic cholinergic receptor: a BOLD phMRI and connectivity study on awake rats - Brems, Brittany M.; Sullivan, Erin E.; Connolly, Jenna G.; Zhang, Jingchun; Chang, Arnold; Ortiz, Richard; Cantwell, Lucas; Kulkarni, Praveen; Thakur, Ganesh A.; Ferris, Craig F. (Frontiers in Neuroscience, 2023)
Background Alpha 7 nicotinic acetylcholine receptor (α7nAChR) agonists have been developed to treat schizophrenia but failed in clinical trials due to rapid desensitization. GAT107, a type 2 allosteric agonist-positive allosteric modulator (ago-PAM) to the α7 nAChR was designed to activate the α7 nAChR while reducing desensitization. We hypothesized GAT107 would alter the activity of thalamocortical neural circuitry associated with cognition, emotion, and sensory perception. Methods The present study used pharmacological magnetic resonance imaging (phMRI) to evaluate the dose-dependent effect of GAT107 on brain activity in awake male rats. Rats were given a vehicle or one of three different doses of GAT107 (1, 3, and 10 mg/kg) during a 35 min scanning session. Changes in BOLD signal and resting state functional connectivity were evaluated and analyzed using a rat 3D MRI atlas with 173 brain areas. Results GAT107 presented with an inverted-U dose response curve with the 3 mg/kg dose having the greatest effect on the positive BOLD volume of activation. The primary somatosensory cortex, prefrontal cortex, thalamus, and basal ganglia, particularly areas with efferent connections from the midbrain dopaminergic system were activated as compared to vehicle. The hippocampus, hypothalamus, amygdala, brainstem, and cerebellum showed little activation. Forty-five min post treatment with GAT107, data for resting state functional connectivity were acquired and showed a global decrease in connectivity as compared to vehicle. Discussion GAT107 activated specific brain regions involved in cognitive control, motivation, and sensory perception using a BOLD provocation imaging protocol. However, when analyzed for resting state functional connectivity there was an inexplicable, general decrease in connectivity across all brain areas.